Seasonality of mortality: the September phenomenon in Mediterranean countries - Falagas, Matthew E. (Canadian Medical Association, 2009)
BACKGROUND: Seasonal increases in the mortality rate have been associated with excessively cold or hot weather. We evaluated monthly patterns of mortality in selected countries. METHODS: We analyzed all-cause mortality statistics from 5 European Mediterranean countries (Cyprus, France, Greece, Italy, Spain), Sweden, North America (United States and Canada), Australia, New Zealand and Japan. We extracted and tabulated data on monthly all-cause mortality in the general population from the earliest to the latest year that records were available. RESULTS: We identified relevant data for a period of 2–57 years in each country. In the Mediterranean countries, the lowest average daily mortality was observed in September (all countries, 125/168 [74%] years). The fewest deaths were in August in Sweden (14/20 [70%] years) and North America (32/50 [64%] years). The fewest deaths in Japan occurred in July (2/2 [100%] years). In the southern hemisphere, the lowest mortality in Australia occurred in March (7/10 [70%] years) and in February for New Zealand (cumulative over 24 years). INTERPRETATION: Mortality in the general population declines in the late summer to early fall months in the countries evaluated. Environmental parameters may partly account for these associations, and further research is needed on the contribution of additional factors such as summer vacations.